Implementasi Model Pembelajaran Think, Pair, Share (TPS) untuk Meningkatkan Partisipasi Aktif Siswa dalam Pembelajaran PKN Kelas VI - Supriadi, Soni (utile: Jurnal Kependidikan, 2025)
This research aims to improve student learning outcomes by using a learning model Think Pair Share (TPS) in PKN subjects with a Classroom Action Research approach. The research subjects were 40 grade VI students at SDN Cilaku 2 consisting of 19 girls and 21 boys. The techniques used by researchers include the stages of planning, action, observation and reflection. The results of observations in cycle I showed that the level of student activity was 61%. Therefore, in cycle I, student activity can be categorized as quite active. Meanwhile in cycle II it increased to 82%. Overall, the use of learning models Think Pair Share (TPS) in PKN learning can be said to be successful with an increase of 21% from cycle I to cycle II.